ONLINE IMPULSE BUYING BEHAVIOUR: CASE STUDY ON USERS OF TOKOPEDIA - Fataron, Zuhdan Ady (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
This article aims to find out the phenomenon of impulsive buying which is influenced by the ease of use and usefulness of information technology that mediates the pleasure of shopping, in this case the writer chooses tokopedia as the object of research. Unplanned buying behavior is an interesting phenomenon to examine because it is a potential for developing market share.The sample determination method used was 149 respondents. The population in this study is Tokopedia online shop users. Data analysis technique uses descriptive analysis, which is to obtain a picture of the respondent's tendency to answer, and inferential analysis to test the model developed, while the analysis technique used is Structural Equation Modeling (SEM).The test results show that the ease of use and usefulness of technology has a positive effect in supporting shopping pleasure, while shopping pleasure can explain the factors that influence impulsive purchases.